In vitro Propagation of a Rare Medicinal Plant Abrus laevigatus E. May - Ranjit Bansode; Vijay Kothekar, Narayan Pandhure*, (Recent Research in Science and Technology, 2010)
Abstract An efficient protocol was developed for in vitro propagation of Abrus laevigatus E. May. through induction of Plantlets by indirect organogenesis in nodal segment derived callus tissues. Yellowish green, fragile, nodular callus was induced at the cut surface of the nodal segments cultured on MS fortified with 5.0 mg/1 BAP, 0.2 mg/l KIN and 0.1 mg/1 IBA. The callus differentiated into adventitious shoots when it was sub-cultured on to MS supplemented with 3.0 mg/l BAP + 0.5 mg/1 Kin + 0.5 mg/1 NAA. On an average 6.87 Â± 0.26 shoots developed. These micro-shoots were rooted in half-strength MS containing 1.0 mg/1 IBA and the rooted plantlets were transferred to soil after acclimatization. Keywords: Abrus laevigatus E. May, In vitro propagation, Callus